Conseptual metaphors of ʽparadiseʼ in the translation of the Quran by Sigitas Geda - Vaivadaitė-Kaidi, Eglė (Lietuvių kalba, 2011)
The article deals with conceptual metaphors of ʽPARADISEʼ in the Lithuanian translation of the Quran on the basis of the conceptual metaphor theory proposed by George Lakoff and Mark Johnson. The aim is to discover to what extent a translation can reveal the linguistic landscape characteristic of a different culture. The research provides a comparison of the translations of the Quran into the Lithuanian (Geda 2008), Spanish (Asad 2001), and English (Ysuf Ali 1998) languages. It is presumed that in the translations of typologically remote languages the recurrent metaphors have most likely been taken from the original, whereas the differences in translation are present due to the linguistic and cultural peculiarities of the target language. The investigation has revealed that translation may only partially disclose the linguistic world view of another culture because in the text of a translation there is always overlap between two cultures; it is a kind of a product of synthesis between two world views. The comparison of different translations has disclosed that the Lithuanian translation is characteristic of some peculiarities which can be ascribed to the search for creativity and individual poetic expression if we consider a metaphor a rhetorical figure. However, if we treat metaphor as a tool for the cognition and expression of a nation’s mentality, such translation does not always perform its key function, i.e. to convey the text of another culture as precisely as possible.